Preparação e caracterização de celulose a partir do pseudocaule da bananeira por hidrólise ácida - Gonçalves, Luísa Maria Nunes [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Brazilian agribusiness generates a large amount of waste during the cycle of a harvest, thus, its use for more noble applications, promotes a valorization of this residual biomass. In banana production, for example, since the fruit represents only 12% of the production and the tree does not permanent for a next harvest, the result is a large production of residue consisting of leaves, stem, heart, stink and pseudocaule. In this context, the present work aims to obtain and characterize micro and nanocellulose from the fibers of the banana pseudocaule, promoting an exploration of these residues and generating socioenvironmental benefits. First pseudocaule fibers were dried, ground, granulometrically graded, treated with 4% (w/v) sodium hydroxide solution for 1 hour at 70 ° C and three times bleached with a 1:1 solution of hydrogen peroxide 24 % (m /v) and 4% NaOH (w /v) for 2 hours at 50°C, with the aim of removing amorphous components such as lignin, hemicellulose, ash and extractives. The extraction of the nanocellulose, from the bleached fibers, was made by acid hydrolysis, with 50% sulfuric acid, 60% and 64% (m /m), at 45°C for 30 min. The samples of the natural fibers, treated and nanocellulose were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), thermogravimetry (TGA / DTG) and Fourier transform non-infrared spectroscopy (FTIR). With the results obtained it was possible to conclude that the chemical treatments were efficient in the removal of the amorphous components, obtaining a fiber three times bleached with initial temperature of degradation of 200°C and crystalline index of 67%. (93%), thermal stability (166°C), the visual appearance in relation to the settling and staining of the suspension, was 64% (w /w) Sulfuric acid at 45 ° C for 30 minutes. In this way, it was ... (Complete abstract click electronic access below)

O agronegócio brasileiro gera uma grande quantidade de resíduos durante o ciclo de uma colheita, sendo assim, sua utilização para aplicações mais nobres, promove uma valorização desta biomassa residual. Na produção de banana, por exemplo, como a fruta representa apenas 12% da planta e a bananeira não permanece para a colheita seguinte, o resultado é uma grande geração de resíduo formado pelas folhas, caule, coração, engaço e pseudocaule. Dentro deste contexto, o presente trabalho visou a obtenção e caracterização de micro e nanocelulose a partir das fibras do pseudocaule da bananeira promovendo assim a exploração destes resíduos e gerando benefícios socioambientais. Primeiramente as fibras do pseudocaule foram secas, moídas, classificadas granulometricamente, tratadas com solução alcalina de hidróxido de sódio 4% (m/v) durante 1 hora a 70°C e três vezes branqueadas com uma solução 1:1 de peróxido de hidrogênio 24% (m/v) e NaOH 4% (m/v) durante 2 horas a 50°C, com o objetivo de remover os componentes amorfos como lignina, hemicelulose, cinzas e extrativos. A extração da nanocelulose, a partir das fibras branqueadas, foi feita por hidrólise ácida, com ácido sulfúrico a 50%, 60% e 64% (m/m), a 45°C por 30 min. As amostras das fibras in natura, tratadas e da nanocelulose foram caracterizadas por microscopia eletrônica de varredura (MEV), difração de raios X (DRX), termogravimetria (TGA/DTG) e espectroscopia no infravermelho por transformada de Fourier (FTIR). Com os resultados obtidos foi possível concluir que os tratamentos químicos foram eficientes na remoção de componentes amorfos, obtendo uma fibra três vezes branqueada com temperatura inicial de degradação de 200°C e índice de cristalinidade de 67%. Dentre as condições de hidrólise ácida utilizadas, a melhor ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Materiais compostos; Branqueamento; Hidrolise; Composite materials